Zinc, copper, CD4 T-cell count and some hematological parameters of HIV-infected subjects in Southern Nigeria - Enosakhare A. Asemota; Ifeyinwa M. Okafor; Henshaw U. Okoroiwu; Ewaro R. Ekong; Stanley Obialor Anyanwu; Esienanwan Esien Efiong; Francis Udomah (Integrative Medicine Research)
Background: Low concentration of trace elements has been associated with poor prognosis and mortality in HIV infection. Methods: A cross sectional study was conducted among 100 HIV-infected subjects (70 were on ART treatment, while 30 were ART naïve). Fifty (50) apparently healthy controls were enrolled. Concentration of serum levels of zinc and copper was done using atomic absorption spectrometric method, while complete blood count was determined using automated blood analyzer. CD4+ T-cell count was done using cyflow cytometer. Aim and setting: The aim of this study was to investigate the level of some trace elements and some hematological parameters of HIV-seropositive subjects attending University of Calabar Teaching Hospital Clinic as well as prevalence of trace elements deficiency and anemic status and compare same with HIV-seronegative control. Results: Mean serum zinc, CD4+ T-cell count, Hb, PCV, RBC, MXD, were significantly (p < 0.05) reduced in the HIV-infected subjects, while copper/zinc ratio, MCV, MCH and platelet count were significantly (p < 0.05) raised in the HIV-infected subjects. The serum Cu level was comparable (p > 0.05) with the control. ART treatment had no effect on all the parameters assessed except CD4+ T-cell count. Twenty five percent (25%), 3% and 56% of the HIV-infected subjects were zinc deficient, copper deficient and anemic, respectively. Gender was found as a predictor of zinc deficiency. Copper and zinc showed weak positive correlation with CD4+ T-cell count. Conclusion: ART treatment did not complement zinc status in HIV infection while improving CD4+ T-cell count, hence the need to consider supplementation. Keywords: Anemia, CD4 count, HIV, Serum zinc, Serum copper